Psychological Problems in English Presentations Experienced by Students of the English Education Study Program at UNU Kalbar - Nizarrahmadi Nizarrahmadi; Dewi Ismu Purwaningsih; Abdul Mujib; Muhammad Sood; Muhammad Yassin; Dita Septiana (Yayasan Pendidikan Bima Berilmu, 2025)
This research investigates the psychological challenges experienced by second-semester students of the English Education Study Program at UNU Kalbar during English presentation activities. A qualitative descriptive method was employed to provide a clear overview of the affective barriers influencing students’ speaking performance. Data were collected through an 18-item questionnaire supported by semi-structured interviews to obtain a comprehensive understanding of their experiences. The analysis focused on six psychological aspects: lack of confidence, shyness, fear of making errors, anxiety, low motivation, and concern about criticism. The findings reveal that many students experience considerable nervousness, hesitation, and reduced motivation when presenting in English. Fear of criticism and low motivation appear as the most dominant barriers. These psychological issues limit students’ ability to express ideas clearly and hinder their overall performance. Therefore, the study recommends that lecturers implement motivational teaching strategies, create supportive and low-stress learning environments, and provide constructive, non-judgmental feedback to help students overcome psychological obstacles and improve their English presentation skills.